2014
DOI: 10.1002/j.1556-6978.2014.00055.x
|View full text |Cite
|
Sign up to set email alerts
|

Pedagogy in Counselor Education: A 10‐Year Content Analysis of Journals

Abstract: This content analysis includes 230 peer-reviewed articles regarding teaching and learning published in journals of the American Counseling Association and its divisions between January 2001 and December 2010. Results include examination of focus, pedagogical foundations, and the methodologies used. Implications for the scholarship of teaching and learning in counselor education are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
86
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(92 citation statements)
references
References 22 publications
5
86
1
Order By: Relevance
“…Scholars have acknowledged concern about the quality of counselor education doctoral students’ preparation for teaching (Barrio Minton, Wachter Morris, & Yaites, 2014). In a 10‐year content analysis of teaching articles in ACA journals, only five articles focused on the preparation of doctoral‐level counselor educators, and only one of the five focused specifically on teacher preparation (Barrio Minton et al, 2014). Additionally, Waalkes et al (2018) explored beginning counselor educators’ teaching preparation and found that the majority of participants thought that there was incongruence between how they were prepared to teach in their doctoral program and the realities of teaching as a counselor educator.…”
mentioning
confidence: 99%
“…Scholars have acknowledged concern about the quality of counselor education doctoral students’ preparation for teaching (Barrio Minton, Wachter Morris, & Yaites, 2014). In a 10‐year content analysis of teaching articles in ACA journals, only five articles focused on the preparation of doctoral‐level counselor educators, and only one of the five focused specifically on teacher preparation (Barrio Minton et al, 2014). Additionally, Waalkes et al (2018) explored beginning counselor educators’ teaching preparation and found that the majority of participants thought that there was incongruence between how they were prepared to teach in their doctoral program and the realities of teaching as a counselor educator.…”
mentioning
confidence: 99%
“…Content analysis is a methodology that includes procedures for making reliable and valid inferences from texts (Krippendorff, 2013). As noted by Barrio Minton, Wachter Morris, and Yaites (2014), content analysis can serve as a methodology to illustrate trends within a profession. Furthermore, content analysis has been commonly used in the examination of counselor education syllabi related to topics such as internship (Akos & Scarborough, 2004), crisis preparation (Barrio Minton & Pease‐Carter, 2011), spirituality (Cashwell & Young, 2004), and multicultural counseling instructional strategies (Priester et al, 2008).…”
Section: Methodsmentioning
confidence: 99%
“…Historically, the counselor education and supervision literature has shown a stark lack of attention to doctoral‐level preparation (Barrio Minton, Wachter Morris, & Yaites, 2014; Barrio Minton et al, 2018). In 2018, the profession saw the emergence of articles on teaching preparation, mentorship of doctoral students, and preparation of supervisors (e.g., Harris et al, 2018; Herbert et al, 2018; Merlin‐Knoblich et al, 2018; Rapp et al, 2018; Waalkes et al, 2018), all areas notably lacking in previous literature.…”
Section: Reflections and Implicationsmentioning
confidence: 99%